PENILAIAN E-MODUL BLUS KERAH SETALI - atikah; Suryawati; Eneng Lutfia Zahra (Practice of Fashion and Textile Education Journal, 2026)
This study aims to obtain assessment results on the e-module learning media for shawl collar blouse. This study uses a pre-experimental method with a one-shot case study research design. The data was analyzed using descriptive quantitative data analysis technique. The data collection procedure involves distributing open-ended and closed-ended questionnaires to panelists consisting of subject matter experts. This study utilised an assessment theory based on the characteristics of a good module, consisting of self-instructional, self-contained, stand-alone, adaptive, and user-friendly, as well as the quality elements of a module, consisting of formatting, organisation, appeals, type and size of font, white space usage, and consistency. The study results based on the characteristics of a good module obtained a percentage of 86.6% and the study results based on the quality elements of the module obtained a percentage of 96.4%. Overall, the feasibility level of the e-module for collared blouses is 91.5%, placing the e-module in the excellent category.